The development and validation of a questionnaire on Root Cause Analysis - Wepener, Clare (Division of Nursing and Midwifery, 2021)
Background: Root Cause Analysis (RCA) is a method of investigating adverse events (AEs). The purpose of RCA is to improve quality of care and patient safety through a retrospective, structured investigative process of an incident, resulting in recommendations to prevent the recurrence of medical errors. Aim: The aim of the study was to develop and validate a prototype questionnaire to establish whether the RCA model and processes employed at the research setting were perceived by the users to be acceptable, thorough and credible in terms of internationally established criteria. Methods: This is a validation study comprising four phases to meet the study objectives: 1) the development of a prototype questionnaire guided by a literature review; 2) assessing the validity of the content of the questionnaire by and numerical evaluation of the face validity thereof; 3) assessing the qualitative face validity cognitive interviews; and 4) reliability by test-retest. Results: Content validity assessment in Phase 2 resulted in removal of 1/36 (2.77%) question items and amendment of 7/36 (19.44%), resulting in 35 for the revised questionnaire. Analysis of data from the cognitive interviews resulted in amendment of 20/35 (57.14%) question items but no removal. Reliability of the final questionnaire achieved the predetermined ≥0.7 level of agreement. Conclusion: The questionnaire achieved a high content validity index and face validity was enhanced by cognitive interviews by providing qualitative data. The inter-rater coefficient indicated a high level of reliability. The tool was designed for a local private healthcare sector and this may limit its use.